Tick Saliva and Salivary Glands: What Do We Know So Far on Their Role in Arthropod Blood Feeding and Pathogen Transmission - Neelakanta, Girish; Sultana, Hameeda (Frontiers in Cellular and Infection Microbiology, 2022)
Ticks are blood-sucking arthropods that have developed myriad of strategies to get a blood meal from the vertebrate host. They first attach to the host skin, select a bite site for a blood meal, create a feeding niche at the bite site, secrete plethora of molecules in its saliva and then starts feeding. On the other side, host defenses will try to counter-attack and stop tick feeding at the bite site. In this constant battle between ticks and the host, arthropods successfully pacify the host and completes a blood meal and then replete after full engorgement. In this review, we discuss some of the known and emerging roles for arthropod components such as cement, salivary proteins, lipocalins, HSP70s, OATPs, and extracellular vesicles/exosomes in facilitating successful blood feeding from ticks. In addition, we discuss how tick-borne pathogens modulate(s) these components to infect the vertebrate host. Understanding the biology of arthropod blood feeding and molecular interactions at the tick-host interface during pathogen transmission is very important. This would eventually lead us in the identification of candidates for the development of transmission-blocking vaccines to prevent diseases caused by medically important vector-borne pathogens.